2013
DOI: 10.11113/jt.v65.2149
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Truck and Cargo Drivers’ Fatigue in Bangladesh

Abstract: In recent studies, it has been observed that fatigue is one of the major factors contributing to fatal accidents in Bangladesh. It is increasing tremendously and alarmingly and causing the huge loss of lives and assets. In Bangladesh, heavy vehicle drivers are susceptible to frequent fatigue related accidents, thus increasing disability and social and economic vulnerability. The study aims to identify truck drivers’ causes of fatigue and other physical, socio-psychological and economic consequences on the driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…[56][57][58] When the number of traffic accidents is examined according to the fatigue levels of the employees, it has been stated that fatigue causes distraction and increases the likelihood of traffic accidents. 31,59,60 A study on fatigue-induced accidents has stated that approximately 83% of drivers in Bangladesh had a direct or indirect fatigue-related crash. 61 Driver fatigue has been identified as a condition that reduces mental alertness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[56][57][58] When the number of traffic accidents is examined according to the fatigue levels of the employees, it has been stated that fatigue causes distraction and increases the likelihood of traffic accidents. 31,59,60 A study on fatigue-induced accidents has stated that approximately 83% of drivers in Bangladesh had a direct or indirect fatigue-related crash. 61 Driver fatigue has been identified as a condition that reduces mental alertness.…”
Section: Discussionmentioning
confidence: 99%
“…Among the factors contributing to fatigue, long working hours is the most important factor. 31,[59][60][61] Lim and Chia 29 have examined the fatigue levels of the employees according to the average working hours, and they have shown that long working hours are an important factor that causes fatigue. The economic burden of taxi drivers leads to longer working hours, which increases the taxi driver's fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Again, 72% of the drivers did not get to go home to spend time with their families. Many drivers sleep inside the vehicle because of the unavailability of cheap rest houses [4]. Most of the drivers in the study did not have fixed salaries, and they were paid per trip.…”
Section: Low-income Frustrationmentioning
confidence: 99%
“…Fatigue is one of the significant factors for fatal accidents in Bangladesh. In Bangladesh, heavy vehicle drivers are prone to frequent fatigue-related accidents, thus increasing disability and social and economic vulnerability [4]. The number of fatalities in road accidents continues to climb, reaching 1.35 million in 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation